Studies of water quality of domestic sewage in the City of João Monlevade - MG, in relation to standards (Research, Society and Development, 2020)
Santary sewage is the main source of contamination of water bodies, the volume released consititutes an expressive load of pathogenic organisms that are transmitted to man through direct ingestion of untreated water, ingestion of contaminated food or by infection resulting from skin contact contaminated water. Thus, in order to know the water quality situation of João Monlevade’s domestic sewers, the present work has emphasized the real need for the implementation and operation of the Sewage Treatment Station in the Cruzeiro Celeste neighborhood. The norms established by COPAM and CONAMA, in addition to conducting a mapping of sewage discharge points and opinion polls involving the riverside population of this region and high school students. The diagnosis of the sewage quality situation was carried out through chemical analysis, mapping using the GPS Trackmaker program and the opinion survey using a questionnaire and an interview. Based on the standards for monitoring water quality and chemical analyzes, the need for the implementation of a Sewage Treatment Plant was proven. The maps enabled the global visualization of the health system, producing information for the population and future research. The opinion poll showed the population’s lack of knowledge about the implementation and operation of the TEE. Thus, the greater the insertion of the community in aspects of public life, the greater the demand for more effective results.